2018
DOI: 10.1093/abm/kax054
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation Predicts Frequent Attendance in Primary Care

Abstract: Unmet social needs among frequent attenders warrant closer consideration. Interventions that target social group connectedness show promise for reducing overutilization of primary care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…Our patient survey allowed us to empirically examine these associations. Our results replicated previous findings showing the importance of group memberships for health service usage (eg, Cruwys et al 12), and we illustrate the predictive direction of this effect, with group memberships predicting increased community belonging, which predicts reduced loneliness. Moreover, these factors serially predict health service use, even when controlling for age, gender, relationship status and education.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our patient survey allowed us to empirically examine these associations. Our results replicated previous findings showing the importance of group memberships for health service usage (eg, Cruwys et al 12), and we illustrate the predictive direction of this effect, with group memberships predicting increased community belonging, which predicts reduced loneliness. Moreover, these factors serially predict health service use, even when controlling for age, gender, relationship status and education.…”
Section: Discussionsupporting
confidence: 90%
“…Our qualitative analyses point to a consensus among GPs, SP staff and patients: loneliness and social isolation—key threats to patient health—can be addressed through SP. In line with research in the social cure tradition which has demonstrated a direct link between lack of social group connectedness and GP attendance,12 the absence of meaningful associative relationships is recognised by these health professionals to have detrimental health effects. Moreover, social isolation was perceived by GPs as being directly related to the frequency of inappropriate usage of primary care services by some patients and SP was recognised as a remedy for this.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Other factors related to DSI such as social isolation, self‐esteem or falls are also discussed as underlying reasons for the association between DSI and HCU. For example, factors such as social isolation have been shown to be associated with increased HCU . However, we additionally adjusted for all of these factors (i.e., falls, self‐esteem, perceived autonomy and social isolation) in a robustness check (results not shown, but available upon request) and our results remained almost the same (for DSI with number of specialist visits as outcome measure, IRR = 1.16 [1.06–1.28], P < 0.01).…”
Section: Discussionmentioning
confidence: 77%
“…Increasing awareness about the importance of screening for (perceived) social isolation in daily practice may help to identify people who may be at high risk of cognitive decline. Indeed, previous studies have demonstrated that individuals with unmet social needs are more likely to be frequent users of health care services . The development of tailored interventions that include the enhancement of social participation and the maintenance of emotionally supportive relationships might contribute to cognitive decline prevention and risk reduction.…”
Section: Discussionmentioning
confidence: 99%